Cases in adversiting and promotion management - Quelch, John A., (Irwin, 1991)
PART 1. Adversiting, promotion and marketing communications ; PART 2. Adversiting, branding, and positioning ; PART 3. Message strategy and copy testing ; PART 4. madia strategy ; PART 5. Budgeting ; PART 6. Sales promotion: strategy and tactics, PART 7. Point-of-Purchase Merchandising ; PART 8. Agency Relations and Management ; PART 9 Social and Ethical Issues ; PART 10. Projects and exercises in Advertising and Promotion Management.